Analysis of the Quality of Teleconsultation Services and the Role of Digital Literacy in Improving Patient Satisfaction - Putri, Chitra Ayu Cempaka; Sarwoko, Endi; Harianto, Eric (Journal Research of Social Science, Economics, and Management, 2026)
Patient satisfaction is an important factor in determining the success and sustainability of teleconsultation services. The ongoing digital transformation in healthcare, along with the increasing use of telemedicine after the COVID-19 pandemic, particularly at Puskesmas Pancoran, highlights that patient satisfaction is a key element in maintaining the continuity of technology-based services. This study aims to examine the effect of teleconsultation service quality on patient satisfaction and to assess the role of digital literacy as a moderating variable.This research adopts a quantitative approach using a survey method involving 123 respondents from a total population of 494 teleconsultation patients, with data analyzed using SmartPLS. The results indicate that teleconsultation service quality has a positive and significant effect on patient satisfaction. However, digital literacy does not function as a moderating variable in this relationship. Nevertheless, digital literacy has a positive and significant direct effect on patient satisfaction. These findings also suggest that service quality plays a more dominant role than digital literacy in determining patient satisfaction. This study has several limitations, including its focus on a single location with relatively homogeneous respondent characteristics and the use of a cross-sectional design, which cannot fully capture changes in patient satisfaction over time. Theoretically, the findings support Social Presence Theory, showing that service quality and digital literacy contribute to shaping patient satisfaction through perceived presence in teleconsultation. Practically, improving service quality, particularly in communication, responsiveness of healthcare providers, system simplification, and strengthening digital literacy are essential to enhance patient satisfaction.